Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s11604-016-0538-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of organized thrombus in distal pulmonary arteries in patients with chronic thromboembolic pulmonary hypertension using cone-beam computed tomography

Abstract: CBCT clearly revealed and classified distal lesions in CTEPH patients. The CBCT findings for distal lesions were highly consistent with those of selective angiography during BPA. CBCT could be a useful modality to detect target lesions before BPA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 13 publications
1
13
0
2
Order By: Relevance
“…Type 1a: webs; type 1b: webs with severe narrowing of the subsegmental artery; type 2: web and slits; type 3: slits; and type 4: pouch defect with incomplete obstruction of subsegmental branches or complete occlusion. >90% of lesions diagnosed by CBCT were consistent with the findings on selective angiography during BPA [57].…”
Section: Imaging For Bpasupporting
confidence: 71%
See 1 more Smart Citation
“…Type 1a: webs; type 1b: webs with severe narrowing of the subsegmental artery; type 2: web and slits; type 3: slits; and type 4: pouch defect with incomplete obstruction of subsegmental branches or complete occlusion. >90% of lesions diagnosed by CBCT were consistent with the findings on selective angiography during BPA [57].…”
Section: Imaging For Bpasupporting
confidence: 71%
“…Cone-beam computed tomography (CBCT) is important for localisation of relevant intra-arterial lesions and the assessment of pulmonary artery diameter. A recent study by FUKUDA et al [57] comparing CBCT with selective angiography during BPA has shown that CBCT can be used to select target lesions in segmental and subsegmental pulmonary artery branches, and gives clearer images of webs and bands than conventional computed tomography angiography. They identified the following lesion types.…”
Section: Imaging For Bpamentioning
confidence: 99%
“…Magnetic resonance imaging of the pulmonary vasculature is still considered inferior to CT [457]. Cone-beam CT [458], angioscopy [459], intravascular ultrasound, and optical coherence tomography are more suitable for the characterization of lesions during interventional treatment than for diagnosis. High-resolution CT scan of the chest may assist in the differential diagnosis of CTEPH, showing emphysema, bronchial, or interstitial lung disease, as well as infarcts, and vascular and thoracic wall malformations.…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%
“…Image merging produces a three-dimensional roadmap that can be used in conjunction with real-time fluoroscopy, and provides the possibility of live monitoring from any angle and magnification. This can provide invaluable guidance for complex pulmonary vascular interventions [48][49][50].…”
Section: Rotational Angiography and Cone Beam Ctmentioning
confidence: 99%